Perception of Therapeutic Conditions as a Function of Perceived Level of Parental Acceptance-Rejection - Lee, Dong Yu; Nevison, Myrne B. (Canadian Journal of Counselling and Psychotherapy, 2012)
The impact of the subject's perceived level of parental acceptance-rejection on his perception of therapeutic conditions in a simulated counseling interview was investigated. It was hypothesized that subjects who report a low level of parental acceptance-affection are unable to per- ceive the counselor-offered therapeutic conditions as the majority or modal group members. Based on the score indicating subject's perception of the counselor responses in video-taped interviews, a total of 222 secondary- school subjects were classified as: High-Perceivers, having perceived high levels of therapeutic conditions (top 33'/r of the sample); Low-Perceivers, having perceived low levels of conditions (bottom 33%); Average-Perceivers, (middle 33%). The dependent variable, the perceived level of parental acceptance-rejection, was compared among the groups. Results: There was no significant difference in the perceived level of parental acceptance- rejection between High- and Average-Perceivers. However, compared to Average-Perceivers, Low-Perceivers indicated a significantly lower level of the mother acceptance-affection.